THE ROLE OF FOLKLORE IN TEACHING LOGICAL THINKING - Toshtemirova Kamola Absattarovna; Pardaeva Aziza Raxmatilloyevna (International Journal of Innovations in Engineering Research and Technology, 2021)
From this paper we will see how through oral folk art, a person not only masters his native language, but also, mastering its beauty, conciseness, gets acquainted with the culture of his people, gets the first ideas about it.